Performance of the ATLAS detector using first collision data - Aad, Georges; Andrei, George Victor; Dietzsch, Thorsten; Hanke, Paul; Khomich, Andrei; Kluge, Eike-Erik; Kugel, Andreas; Männer, Reinhard; Meier, Karlheinz; Müller, Felix; Poddar, Sahill; Radescu, Voica; et al. (Journal of high energy physics, 2010)
More than half a million minimum-bias events of LHC collision data were collected by the ATLAS experiment in December 2009 at centre-of-mass energies of 0.9 TeV and 2.36 TeV. This paper reports on studies of the initial performance of the ATLAS detector from these data. Comparisons between data and Monte Carlo predictions are shown for distributions of several track-and calorimeter-based quantities. The good performance of the ATLAS detector in these first data gives confidence for successful running at higher energies.
Gesehen am 31.10.2022
*The ATLAS collaboration: G. Aad, V. Andrei, T.A. Dietzsch, P. Hanke, A. Khomich, E.-E. Kluge, A. Kugel, R. Maenner, K. Meier, F. Mueller, S. Poddar, V. Radescu, S. Schaetzel, V. Scharf, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und sehr viele weitere Personen]